Smoke cessation in cardiovascular pathology from the perspective of evidence-based medicine - O. A. Sukhovskaya; N. V. Kulikov (Российский кардиологический журнал, 2019)
The effectiveness of smoking cessation methods has been studied in various studies. However, little is known about the peculiarities of treatment of nicotine dependence in patients with cardiovascular diseases. In the presented review, according to the literature, the prevalence and characteristics of smoking, the duration of abstinence from smoking in patients with cardiovascular diseases with different methods of quitting tobacco use are described.It is shown that smoking cessation not only shows long-term positive effects, but almost immediately the supply of cells with oxygen increases, platelet aggregation, fibrinogen synthesis decreases. Carrying out treatment for nicotine addiction, especially when combined with behavioral support, significantly increases the effectiveness of quitting smoking. With the cardiovascular pathology, the efficacy and safety of varenicline has been proven.